Managing Creative Entrepreneurship in the Arts: A Dual-Path Conceptual Model for Traditional Crafts and Short-Video Ventures in University Incubators (China with Global Relevance) - Wang, Pengyu (International Journal of Multidisciplinary Research, 2026)
University incubators increasingly support arts-based ventures, yet these entities are often treated as a monolithic category. This approach overlooks critical differences in production systems, intellectual property regimes, and distribution channels. This paper proposes a dual-path conceptual model to explain how artistic creativity transforms into sustainable entrepreneurial value. It distinguishes between craft-based ventures (e.g., lacquerware, metalwork), which rely on material authenticity and tacit skills, and platform-based digital ventures (e.g., short-video studios), which depend on algorithmic attention and rapid iteration. Drawing on exploration–exploitation theory and the resource-based view, the model identifies distinct development mechanisms for each path. The study argues that effective incubation requires differentiated support structures rather than a uniform startup toolkit. While grounded in the Chinese university context, the model offers relevant insights for arts incubation globally.